2017
DOI: 10.5455/jcme.20170612092613
|View full text |Cite
|
Sign up to set email alerts
|

Health habits of medical students during operating room rotations

Abstract: METHODSWe selected several lifestyle factors to study, which included exercise, sleep, diet, caffeine consumption, and alcohol consumption. These factors were chosen because public health organizations identify them as risk factors for the most common chronic diseases (i.e., cancer, cardiovascular disease, diabetes, and chronic respiratory diseases) [16]. Evidence that each lifestyle factor was being optimized for health was indicated through compliance with a guideline for healthy living related to this facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Fifty-six percent ( n = 22) have dreaded going to work due to uncivil behavior in the operating room. Similar to the findings of Hamlin et al (2016), Garth et al (2019) found that uncivil behaviors were reported most commonly as being committed by operating room physicians and nurse colleagues. The most common reported uncivil behavior by fellow operating room nurses was gossiping about other nurses, with 83.79% ( n = 31).…”
Section: Methodological Approachessupporting
confidence: 73%
See 4 more Smart Citations
“…Fifty-six percent ( n = 22) have dreaded going to work due to uncivil behavior in the operating room. Similar to the findings of Hamlin et al (2016), Garth et al (2019) found that uncivil behaviors were reported most commonly as being committed by operating room physicians and nurse colleagues. The most common reported uncivil behavior by fellow operating room nurses was gossiping about other nurses, with 83.79% ( n = 31).…”
Section: Methodological Approachessupporting
confidence: 73%
“…It was concluded that the low-ubiquity results reveal that only a small number of operating room professionals engage in the perpetration of negative behaviors. Although surgeons were viewed to be the most persistent perpetrators, involvement from members of all professions strongly suggests that generalized “prophylactic interventions” may be useful in the reduction of the frequency of these negative behaviors (Hamlin et al, 2016). These findings are similar to those of Katz et al (2019) in that assertiveness training and/or civility training is needed in order to defend against uncivil behavior in the operating room.…”
Section: Methodological Approachesmentioning
confidence: 99%
See 3 more Smart Citations